Comparison of Ephedrine Versus Crystalloid Preload in Prevention of Hypotension after Spinal Anesthesia for Cesarean Section - Amin, Khalid; Wadud, Roheena; Ikram Ullah; Khan, Muhib Ullah; Shafi Ullah (Indus Journal of Bioscience Research, 2025)
Background: Spinal anesthesia is commonly used for cesarean delivery because it is simple, quick, and safe for both the mother and fetus compared with other methods like general anesthesia. However, maternal hypotension is the most common side effect experienced by a woman who has undergone spinal anesthesia for a cesarean delivery. Hypotension can cause distress and decreased uteroplacental perfusion. Several methods are used for prevention but their effectiveness is questionable. Objective: To compare the efficacy of ephedrine versus crystalloid preload in prevention of hypotension after spinal anesthesia for cesarean section. Study Design: Randomized controlled trial. Duration and Place of Study: This study was conducted from 10 July 2024 to 10 January 2025 in the Department of Anesthesia, Lady Reading Hospital, Peshawar. Methodology: A total of 130 pregnant women aged 20 to 40 years undergoing elective cesarean section were included and randomly divided into two equal groups. One group received crystalloid preload while the other group received prophylactic ephedrine. Maternal blood pressure was monitored at regular intervals after spinal anesthesia. Hypotension was defined as blood pressure less than 100/60 millimeters of mercury. Chi square test were used with p value ≤0.05 considered significant. Results: Hypotension occurred in 35.4% patients in crystalloid group and 15.4% patients in ephedrine group showing significant difference with p value of 0.009. Conclusion: Ephedrine is more effective than crystalloid preload in preventing hypotension after spinal anesthesia during cesarean section.